Rola carycy Marii-Ireny Lekapeny w recepcji elementów bizantyńskiego modelu władzy w pierwszym państwie bułgarskim - Brzozowska, Zofia A. (Vox Patrum, 2016)
Maria Lekapene was the granddaughter of Byzantine Emperor Romanos I Lekapenos. In 927 she married Peter I of Bulgaria. Her marriage in Constantinople aimed to strengthen the newly signed Byzantine-Bulgarian peace treaty. Historians attributed to the Empress a significant impact on the political moves of her husband. The Empress was also to introduce a lot of elements of the Byzantine theory of power in Bulgaria and even to play the role of spy of Constantinople at the Preslav court. These views have not been corroborated in surviving source material. The Byzantine authors, who provided a lot of information about the wedding of Maria and Peter, did not write anything about the subsequent behavior of the Empress in her new homeland. The political activity of the wife of Peter is not mentioned in indigenous Bulgarian sources or foreign ones (e.g. Liutprand of Cremona). The thesis that Maria wielded real political power can be confirmed only in sigillographic materials. In 927-945 the Bulgarian ruler was always represented on his own official seals accompanied by his wife. However it was not a reflection of her status as a real co-emperor. These seals were propagandic artifacts which were made to commemorate the peace of 927. The seals could also be seen as a tool legitimizing the imperial title of Peter. It is hard to consider Mary as the initiator of the Byzantinization of the culture of tenth-century Bulgaria. In 927 Lekapene arrived at the court, which was already quite familiar with the Byzantine civilization. This does not exclude the possibility of her personal impact on the new court. However, most likely the impact did not go beyond the walls of the Emperor’s headquarters.